Repositioning Nigeria Towards Sustainable National Integration Through National Orientation Agency - Osimen, Goddy Uwa; Akintoye, Festus Ayodeji; Adi, Isaac (African Journal of Stability and Development (AJSD), 2022)
Threats of disunity keep ravaging Nigeria’s independence since 1960. The need for disintegration from the nation grows over time especially from the south-eastern and southsouthern regions of the country, and this eventually resulted in Nigeria’s civil war of 1967-1970. Hostilities promoted by ethnic tensions are also higher than ever before. Insurgency which started in the north-eastern region since 2009 has continued to claim several lives and properties till date. Herdsmen and farmers conflicts have also continue to escalate in the north-central region of the country. While, cattle rustling and armed banditry keeps growing in the northwestern region. Attacks and bombardments of oil facilities have been employed by aggrieved militants in the Niger Delta Region to get at the country. Religious intolerance has also continued to result in confrontations that often claim several lives across the northern region of the country. The thrust of this paper is hinged on these threats that have been confronting Nigeria’s national unity. The paper appraises efforts of the National Orientation Agency (NOA) in the task of promoting national integration in Nigeria. Descriptive analysis was adopted in this paper and data were sourced through secondary means from journal articles, magazines, newspapers, bulletins, lecture notes, diaries, and the internet. The paper revealed some of the impediments to national integration in Nigeria to include but not limited to: politics of identity, corruption among the political elites, power struggle and allocation of resources to the federating unions, religious intolerance, and internal conflicts as well as overcentralisation of power. Recommendations were then made towards repositioning the country’s sustainable national unity.